Rotatable magnetic anisotropy in a Fe 0.8 Ga 0.2 thin film with stripe domains: Dynamics versus statics - Tacchi, S. (2014)
A comprehensive investigation of rotatable anisotropy in a Fe0.8Ga0.2 thin film with a stripe domain structure has been performed comparing static and dynamic measurements. The stripes domain formation and their rotation under a transverse magnetic field have been imaged by magnetic force microscopy. The rotatable anisotropy field Hrot was determined by fitting the frequency evolution of the dipole-dominated magnetostatic spin-wave mode versus the in-plane orientation of the stripe domains, measured by Brillouin light scattering in the absence of any dc or ac magnetic field. We obtained Hrot aproximately 1.35 kOe, which is nearly ten times larger than the crystallographic in-plane anisotropy field. By applying a dc magnetic field along the stripes axis, Hrot decreases, and eventually vanishes for saturated in-plane magnetization. At remanence, we established a quantitative relationship between static and dynamic properties, that is, the stripes rotation angle and the in-plane angle dependence of spin-wave frequency.